2021
DOI: 10.2478/enr-2021-0014
|View full text |Cite
|
Sign up to set email alerts
|

Does thyroid dysfunction influence inflammatory mediators in experimental periodontitis?

Abstract: Objective. The aim of the present study was to investigate the presence of inflammatory mediators in rats with only periodontitis and periodontitis in a setting of hyper- and hypo-thyroidism and to analyze the correlative linkages between inflammatory mediators and thyroid hormones. Methods. White male 12–14 weeks old inbred rats (n=48) weighing 180–200 g were employed in the experiment. They were randomly divided into the following groups: Group I – control group, Group II – … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 44 publications
(36 reference statements)
0
9
0
Order By: Relevance
“…In this context, it is not surprising that patients with HT show a pronounced destruction of respective connective tissues [ 8 ]. The second approach is the influence of HT on the PD-related immune response; in experimental PD, thyroid dysfunction was found to foster cytokine imbalance and severity of inflammation [ 14 ]. In addition to that, a potential role of vitamin D in the interplay between PD and HT was reported [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this context, it is not surprising that patients with HT show a pronounced destruction of respective connective tissues [ 8 ]. The second approach is the influence of HT on the PD-related immune response; in experimental PD, thyroid dysfunction was found to foster cytokine imbalance and severity of inflammation [ 14 ]. In addition to that, a potential role of vitamin D in the interplay between PD and HT was reported [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, thyroid autoimmunity was also found to be related to psoriasis [ 23 ]. Considering this, the potential role of LCE family as cross-talk genes between PD and HT would most likely indicate an increase of (auto-) immunity; this is supported by the upper mentioned fact that the thyroid dysfunction would foster cytokine imbalance and severity of periodontal inflammation [ 14 ]. Furthermore, the biological processes immune system process and complement, which were identified as potentially relevant in the current study, would be in line with this hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were randomly divided into four groups (n = 12 per group): group 1 -control, group 2 -rats with a model of periodontitis. For two weeks, the animals were injected with 40 μl (1 mg/ml) of E. coli lipopolysaccharide (LPS) (Sigma-Aldrich, USA) into gingival tissues every other day [6]. Group 3 included rats with HHcy (n = 12).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, in European countries, the incidence of severe periodontitis in the cohort of 35-44 year old adults ranges from 5 to 20%, increasing to 40% in older population groups [4,5]. At the same time, the frequency of periodontal disease among an adult population in Ukraine reaches 85-95% [6].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that thyroid disorders are associated with an increased prevalence rate of periodontal inflammation and tissue destruction, measured by clinical parameters and inflammatory markers. This correlative relationship is more evident in hyperthyroidism populations than in those with hypothyroidism [ 95 , 96 ]. The results of animal studies corroborate clinical findings.…”
Section: Hormonesmentioning
confidence: 99%